Translational Radiobiological Boron Neutron Capture Therapy (BNCT) Studies for the Treatment of Different Pathologies: A Bench to Bedside Approach - Schwint, Amanda Elena; Monti Hughes, Andrea; Garabalino, Marcela Alejandra; Pozzi, Emiliano César Cayetano; Heber, Elisa Mercedes; Trivillin, Verónica Andrea (Austin Publications LLC, 2018)
Fil: Schwint, Amanda Elena. Comisión Nacional de Energía Atómica. Gerencia de Area de Aplicaciones de la Tecnología Nuclear. Gerencia de Radiobiología (Centro Atómico Constituyentes); Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina